MOLECULARLY IMPRINTED POLYMER FOR THE BINDING AND RECOGNITION OF BASIC BLUE 41 DYE - María Guadalupe Sánchez; Elisa Garza; Nancy Pérez; Bernabé L. Rivas; Perla Elizondo (Journal of the Chilean Chemical Society, 2021)
This study reports a novel imprinted molecular poly(ethylene terephatalate) (MIPBB41) for the binding and selective recognition of an azoic dye (basic blue 41) by a non-covalent imprinting approach. Basic blue 41 (BB41) was chosen as the template molecule, acrylic acid-grafted polyethylene terephthalate (PET-g-AA), and N,N’-methylene-bis-acrylamide (MBA) were used as the functional polymer and crosslinking reagent respectively. To determine the binding capacity of MIPBB41, several adsorption studies were performed. The adsorption isotherm was described by the Langmuir model, and the maximum adsorption capacity of MIPBB41 toward basic blue 41 reached 144.8 mg g-1in water at pH 6.2. The fabricated MIP showed good recognition properties. In a further experiment, the adsorption capacity of the MIP was compared to the non-imprinted polymer (NMIP), and a recognition coefficient of 3.14 was obtained.